2023
DOI: 10.1021/acsnano.3c00093
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Endogenous Reactive Oxygen Species Removal and Regulating Regenerative Microenvironment at Annulus Fibrosus Defects Promote Tissue Repair

Abstract: The excessive reactive oxygen species (ROS) level, inflammation, and weak tissue regeneration ability after annulus fibrosus (AF) injury constitute an unfavorable microenvironment for AF repair. AF integrity is crucial for preventing disc herniation after discectomy; however, there is no effective way to repair the AF. Herein, a composite hydrogel integrating properties of antioxidant, anti-inflammation, and recruitment of AF cells is developed through adding mesoporous silica nanoparticles modified by ceria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…ROS play critical roles in the pathogenesis of IDD by causing OS damage and activating crucial signals related to inflammatory response, senescence, and apoptosis. , Here, we designed a core–shell structured PDA@CNO nanoparticle with multiple enzyme-like activities (Figure A), expecting to effectively mitigate the ROS level in the microenvironment of degenerated IVD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS play critical roles in the pathogenesis of IDD by causing OS damage and activating crucial signals related to inflammatory response, senescence, and apoptosis. , Here, we designed a core–shell structured PDA@CNO nanoparticle with multiple enzyme-like activities (Figure A), expecting to effectively mitigate the ROS level in the microenvironment of degenerated IVD.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of IDD featuring reduced NP cells with decreased extracellular matrix (ECM) synthesis has yet to be revealed clearly, but it has been confirmed that oxidative stress (OS) and chronic inflammation often occur concurrently in the microenvironment of degenerated IVD. Cell therapy has recently been applied to treat IDD for enhancing the NP cell number and ECM synthesis but failed to get the desired results, which is ascribed to the low proliferative index of NP cells and the difficulty in directed differentiation of stem cells in such pathological conditions. , Therefore, many efforts have turned to deal with the chronic inflammation and OS in the microenvironment of IDD, expecting to slow down or restrain the degeneration process. , Local injection of anti-inflammatory and antioxidative drugs is the commonly used strategy to treat IDD, but it fails to release in vivo in the long term . As above-mentioned, inflammation generally coexists with OS in the degenerated IVD, so adjusting the OS to a normal level, in turn, may mitigate the inflammatory response for combating IDD .…”
Section: Introductionmentioning
confidence: 99%
“…f) Immunofluorescence of collagen type I. Reproduced with permission. [ 57 ] Copyright 2023, American Chemical Society.…”
Section: Design Strategies and Applications Of Antioxidant Hydrogelsmentioning
confidence: 99%
“…In another study, Han and co‐workers loaded ultrasmall nanoceria and transforming growth factor β3 (TGF‐β3) on the surface of homogeneous mesoporous silica nanoparticles to prepare multifunctional nanoparticles (C‐MSN‐T). [ 57 ] TGF‐β3 could regulate cell proliferation, migration, and matrix secretion. [ 175 ] Subsequently, GelMA and hyaluronic acid methacrylate (HAMA) were loaded with C‐MSN‐T to obtain composite hydrogels (C‐MSN‐T/G‐H) ( Figure a).…”
Section: Design Strategies and Applications Of Antioxidant Hydrogelsmentioning
confidence: 99%
“…Hydrogels with good biocompatibility can be designed to mimic extracellular matrix and they are widely used in biomedicine, especially in regenerative medicine [14][15][16]. Hydrogels can be injected In situ to fill defects, providing the advantages of targeted therapy, less invasiveness, high safety, and easy handling.…”
Section: Introductionmentioning
confidence: 99%